A meta‐analysis of zooplankton functional traits influencing ecosystem function. Issue 4 (8th April 2016) - Hébert, Marie‐Pier; Beisner, Beatrix E.; Maranger, Roxane
Abstract: The use of functional traits to characterize community composition has been proposed as a more effective way to link community structure to ecosystem functioning. Organismal morphology, body stoichiometry, and physiology can be readily linked to large‐scale ecosystem processes through functional traits that inform on interspecific and species‐environment interactions; yet such effect traits are still poorly included in trait‐based approaches. Given their key trophic position in aquatic ecosystems, individual zooplankton affect energy fluxes and elemental processing. We compiled a large database of zooplankton traits contributing to carbon, nitrogen, and phosphorus cycling and examined the effect of classification and habitat (marine vs. freshwater) on trait relationships. Respiration and nutrient excretion rates followed mass‐dependent scaling in both habitats, with exponents ranging from 0.70 to 0.90. Our analyses revealed surprising differences in allometry and respiration between habitats, with freshwater species having lower length‐specific mass and three times higher mass‐specific respiration rates. These differences in traits point to implications for ecological strategies as well as overall carbon storage and fluxes based on habitat type. Our synthesis quantifies multiple trait relationships and links organisms to ecosystem processes they influence, enabling a more complete integration of aquatic community ecology and biogeochemistry through the promising use of effect traits.